Aggregation Operators for Various Extensions of Fuzzy Set and Its Applications in Transportation Problems - Mishra, Akansha; Kumar, Amit.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book introduces readers to the fundamentals of transportation problems under the fuzzy environment and its extensions. It also discusses the limitations and drawbacks of (1) recently proposed aggregation operators under the fuzzy environment and its various extensions; (2) recently proposed methods for solving transportation problems under the fuzzy environment; and (3) recently proposed methods for solving transportation problems under the intuitionistic fuzzy environment. In turn, the book proposes simplified methods to overcome these limitations. .
Chapter 1. Appropriate Weighted Averaging Aggregation Operator Under Some Extensions of the Fuzzy Environment -- Chapter 2. Mehar Method to Find a Unique Fuzzy Optimal Value of Balanced Fully Triangular Fuzzy Transportation Problems -- Chapter 3. Vaishnavi Approach for Solving Triangular Intuitionistic Transportation Problems of Type-2 -- Chapter 4. JMD Approach for Solving Unbalanced Fully Trapezoidal Intuitionistic Fuzzy Transportation Problems -- Chapter 5. JMD Approach for Solving Unbalanced Fully Generalized Trapezoidal Intuitionistic Fuzzy Transportation Problems.
Keywords: Computational intelligence; Artificial intelligence; Transportation engineering; Traffic engineering; Operator theory; Computational Intelligence; Artificial Intelligence; Transportation Technology and Traffic Engineering; Operator Theory